Grandparents Raising Grandchildren: Custody Options - Larry F. Forthun; Millie Ferrer-Chancy (EDIS)
Grandparents have several custody options when they are caring for their grandchildren. To decide which options match your needs, you must become familiar with legal terms. This 2-page revised brochure provides information on custody options, situation scenarios, and legal resources. Written by Larry F. Forthun and Millie Ferrer-Chancy with assistance from the Legal Aid Foundation, and published by the UF Department of Family, Youth and Community Sciences, December 2015.